2021
DOI: 10.3390/antibiotics10060748
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Anti-Microbial Resistance (AMR) Profiling of Methicillin-Resistant Staphylococcus aureus (MRSA) from Hospital and Long-Term Care Facilities (LTCF) Environment

Abstract: To provide evidence of the cross-contamination of emerging pathogenic microbes in a local network between long-term care facilities (LTCFs) and hospitals, this study emphasizes the molecular typing, the prevalence of virulence genes, and the antibiotic resistance pattern of methicillin-resistant Staphylococcus aureus. MRSA isolates were characterized from 246 samples collected from LTCFs, medical tubes of LTCF residents, and hospital environments of two cities, Chiayi and Changhua. Species identification, mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Recent studies also showed a high prevalence of SCCmec IV in the MRSA isolates from poultry and livestock foods, which supports the present study [ 44 , 45 ]. Our previous report about the Chiayi’s river basin and nearby livestock areas revealed that SCCmec IV and I were distributed as 64.1% and 15.4%, respectively, wherein LA and HA-MRSA were predominant isolates from water samples, whereas CA and HA-MRSA were predominant isolates from hospital and long-term care facilities environments [ 46 , 47 ]. In the present case, SCCmec type I (HA-MRSA) was present in the bioaerosol and stool samples, which could be a future threat to the human population.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also showed a high prevalence of SCCmec IV in the MRSA isolates from poultry and livestock foods, which supports the present study [ 44 , 45 ]. Our previous report about the Chiayi’s river basin and nearby livestock areas revealed that SCCmec IV and I were distributed as 64.1% and 15.4%, respectively, wherein LA and HA-MRSA were predominant isolates from water samples, whereas CA and HA-MRSA were predominant isolates from hospital and long-term care facilities environments [ 46 , 47 ]. In the present case, SCCmec type I (HA-MRSA) was present in the bioaerosol and stool samples, which could be a future threat to the human population.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA of MRSA was extracted using a commercial DNA extraction kit (MagPurix Bacterial DNA Extraction Kit, ZP02006), following the protocol described in previous studies [ 2 , 11 ]. After that, different molecular typing experiments were performed via PCR analysis to characterize the MRSA isolates.…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotic-resistant strains of Gram-positive pathogens, especially S. aureus , have been isolated from diverse environments such as hospitals, long-term care facilities, rivers, sediments, lakes, soil, and even the deep ocean [ 1 , 2 ]. However, bioaerosol-associated risk related to S. aureus remains to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations